How coping styles moderate the relationship between diabetes distress and self-care in adults with diabetes in Appalachian Ohio: A cross-sectional survey study - Elizabeth A. Beverly; Samuel Miller; Lauren Schmidtgesling; Kacey Whistler (PLoS ONE, 2025)
Background Diabetes distress is highly prevalent among adults with type 1 and type 2 diabetes, and is associated with fewer self-care behaviors, higher A1C values, increased complications, and lower quality of life. The purpose of this study was to confirm the moderating role of problem-based and emotion-based coping styles in the relationship between diabetes distress and self-care among adults living in Appalachian Ohio. We hypothesized that problem-based coping buffered, while emotion-based coping exacerbated the negative impact of diabetes distress on self-care. Methods Participants completed a series of psychosocial questionnaires, including the Diabetes Distress Scale, Coping Styles, and Self-Care Inventory-Revised. We conducted hierarchical multiple regression models using SPSS version 29.0. Results A total of 256 adults (mean age = 42.6 ± 18.7 years, 62.1% women, 61.3% type 2 diabetes, A1C=7.5 ± 1.5%, mean duration = 12.1 ± 8.9 years) participated. In the type 1 diabetes model, the two-way interactions between problem-based coping and diabetes distress (B = 0.611, p = 0.011) and emotion-based coping and diabetes distress (B = 0.379, p = 0.017) were significant with diabetes self-care (R2 Δ = 0.105, p = 0.002); the effect size was F 2 = 0.290, indicating a medium effect. In the type 2 diabetes model, the two-way interaction between problem-based coping and diabetes distress (B = 0.388, p = 0.012) was significant with diabetes self-care (R2Δ=0.044, p = 0.018); the effect size was F 2 = 0.198, indicating a medium effect. Conclusions Our findings suggest that higher levels of problem-based coping buffered the negative effect of diabetes distress on self-care behaviors in both type 1 and type 2 diabetes. In contrast, emotion-based coping amplified the negative effect of diabetes distress on self-care behaviors, but only in participants with type 1 diabetes. These findings align with previous research and intervention studies focused on coping strategies and diabetes distress.